Effective school leadership enactment of GAI: a 5C’s framework for integration - Ghamrawi, Norma; Shal, Tarek; Ghamrawi, Najah A. R. (Frontiers in Education, 2025)
IntroductionThe integration of Generative Artificial Intelligence (GAI) into educational settings is rapidly transforming teaching and learning processes. As this shift unfolds, school leadership plays a pivotal role in ensuring the effective and ethical adoption of GAI technologies. This study investigates the leadership traits and practices essential for guiding GAI implementation in schools within the Arab region.MethodsA qualitative research design was employed, utilizing semi-structured interviews with 12 school principals from six Arab countries. All participants had led GAI integration initiatives in their schools over the past two years. Data were analyzed thematically to identify patterns in leadership behavior and strategy.ResultsAnalysis revealed five core leadership roles, summarized in the 5 C’s framework: Catalysts for innovation, Curators of GAI technologies, Champions of its benefits, Cultivators of a culture of experimentation, and Connectors fostering collaboration. These roles reflect the multifaceted responsibilities of school leaders in the context of GAI.DiscussionThe findings highlight that effective school leadership in the AI era requires more than technological literacy—it demands visionary, collaborative, and adaptive leadership. The proposed 5 C’s framework provides a strategic model for guiding school leaders in fostering meaningful and sustainable GAI integration. These insights have broad implications for leadership development and policy in AI-informed education.